MESSENGER observations of induced magnetic fields in Mercury's core. Issue 6 (16th March 2016) - Johnson, Catherine L.; Philpott, Lydia C.; Anderson, Brian J.; Korth, Haje; Hauck, Steven A.; Heyner, Daniel; Phillips, Roger J.; Winslow, Reka M.; Solomon, Sean C.
Abstract: Orbital data from the Magnetometer on the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft allow investigation of magnetic fields induced at the top of Mercury's core by time‐varying magnetospheric fields. We used 15 Mercury years of observations of the magnetopause position as well as the magnetic field inside the magnetosphere to establish the presence and magnitude of an annual induction signal. Our results indicate an annual change in the internal axial dipole term, g 1 0, of 7.5 to 9.5 nT. For negligible mantle conductivity, the average annual induction signal provides an estimate of Mercury's core radius to within ±90 km, independent of geodetic results. Larger induction signals during extreme events are expected but are challenging to identify because of reconnection‐driven erosion. Our results indicate that the magnetopause reaches the dayside planetary surface 1.5–4% of the time. Key Points: MESSENGER data reveal magnetic fields induced at the top of Mercury's core The annual induction signal constrains Mercury's core radius to within ±90 km Mercury's magnetopause reaches the dayside planetary surface 1.5–4% of the time